Sodium Oxalate-Induced Acute Kidney Injury Associated With Glomerular and Tubulointerstitial Damage in Rats - de Araújo, Larissa; Costa-Pessoa, Juliana Martins; de Ponte, Mariana Charleaux; Oliveira-Souza, Maria (Frontiers in Physiology, 2020)
Acute crystalline nephropathy is closely related to tubulointerstitial injury, but few studies have investigated glomerular changes in this condition. Thus, in the current study, we investigated the factors involved in glomerular and tubulointerstitial injury in an experimental model of crystalline-induced acute kidney injury (AKI). We treated male Wistar rats with a single injection of sodium oxalate (NaOx, 7 mg∙100 g-1∙day-1, resuspended in 0.9 % NaCl solution, i.p.) or vehicle (control). After 24 h of treatment, food and water intake, urine output, body weight gain and renal function were evaluated. Renal tissue was used for the morphological studies, quantitative PCR and protein expression studies. Our results revealed that NaOx treatment did not change metabolic or electrolyte and water intake parameters or urine output. However, the treated group exhibited tubular calcium oxalate (CaOx) crystals excretion, followed by a decline in kidney function demonstrated along with glomerular injury, which was confirmed by increased plasma creatinine and urea concentrations, increased glomerular desmin immunostaining, nephrin mRNA expression and decreased WT1 immunofluorescence. Furthermore, NaOx treatment resulted in tubulointerstitial injury, which was confirmed by tubular dilation, albuminuria, increased Kim-1 and Ki67 mRNA expression, decreased megalin and Tamm-Horsfall protein (THP) expression. Finally, the treatment induced increases in CD68 protein staining and MCP-1, IL-1β and α-SMA mRNA expression, which are consistent with proinflammatory and profibrotic signaling, respectively. In conclusion, our findings provide relevant information regarding crystalline-induced AKI, showing strong tubulointerstitial and glomerular injury with a possible loss of podocyte viability.